Psychometric properties of depression anxiety stress scale 21-item (DASS-21) Malay version among a big sample population - Musa, Ramli; Maskat, Ruhaila (University of Messina, 2020)
Establishing the psychometric properties of a measurement tool is paramount in order to determine the validity of any study results. The Depression Anxiety Stress Scale (DASS)-21 has preliminary evidence of a good tool in Malaysia. This study among a very big sample size would further strengthen this evidence. Objectives: To validate the DASS-21 Malay version among 367, 860 completed online assessment by looking at its Exploratory Factor Analysis and Construct validity. Methodology: The data was captured through online web-based assessment. Incomplete entries were excluded and analysis was based on 367, 860 completed entries which fulfilled the inclusion criteria. We obtained Cronbach’s alpha values of 0.95, 0.85 and 0.87 respectively for Depression, Anxiety and Stress domains. Rotated component analysis showed very good factor loading for most items to their respective domains. The non-fixed analysis showed the Malay DASS-21 consisted of 2 domains and Stress items loaded equally to Depression and Anxiety domains. The current findings further enhanced the evidence that (DASS)-21 is an excellent tool for Malaysians.